Analisis Perlindungan Produk Garmen Di Industri Dalam Negeri Terhadap Import Pakaian Bekas (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The existence of acceptance of imported used clothing in society is a serious enough problem in an industry, especially in the garment industry, many people prefer imported used clothing to local products making it a challenge for the garment industry to be able to compete with the used clothing market which has become the idol of society lately This. In fact, the government has been intensifying regulations regarding the banning of imports of used clothes for a long time to help industrial parties keep their businesses running. However, the demand for the garment industry is decreasing day by day, so strong protection is needed for garment products to survive in the domestic market. So the authors are very interested in conducting studies regarding the rise of imported clothing which is increasingly troubling the industry, both garment and textile. This study uses a normative legal research method that conducts empirical studies. The results of this study show that there are a lot of government regulations that have been issued regarding imported clothing, both the impact and the way to solve them. In addition, the author also provides an understanding of the economic review of the laws put forward by the ministers and the solutions that must be faced by the garment industry.